An Icon of Lifelong Learning - The, Star (The Star, 2019)
Asia e University (AeU) is among the academic institutions selected as the Lifelong Learning Icon for the year 2019. This year. the programme organised by the Ministry of Education (MoE) has nominated several local icons from numerous backgrounds with the goal to celebrate inspiring icons and cultivate the lifelong learning culture in Malaysia to motivate the young generation to pursue academic excellence regardless of time frame and age.